Multi-objective optimization of a hybrid system based on combined heat and compressed air energy storage and electrical boiler for wind power penetration and heat-power decoupling purposes. (February 2023) - Zhao, Pan; Gou, Feifei; Xu, Wenpan; Shi, Honghui; Wang, Jiangfeng
Abstract: Faced with uncertain heating supply task in heating season, the combined heat and power (CHP) unit groups in "Three North Areas" of China with considerable capacity of wind power often operate in heat-controlled mode with limited flexibility, which exacerbates the wind power curtailment. In order to further improve the operation flexibility of CHP unit group and the wind power penetration level, a hybrid system based on CHP unit group embedded with electrical boiler subsystem and combined heat and compressed air energy storage (CH-CAES) subsystem is proposed. A novel operation strategy on power generation side considering device reserve constraints and transient behaviors is put forward. Then, a bi-level optimization algorithm based on multi-objective particle swarm optimization (MOPSO) and technique for order preference by similarity to an ideal solution (TOPSIS) method is utilized. Finally, a completed heat season case is conducted to investigate the dynamic behaviors and the performance of the improved system. The simulation results of optimal plan mainly dominated by ratio of abandoned wind (ROAW) show that energy and exergy efficiencies with remaining stored energy can be improved by 3.52 % and 2.86 % compared with the basic system, respectively. For the economic performance, the levelized cost of heat (LCOH) drops by 43.56 % while levelized cost of electricity (LCOE) increases by 4.99 %. In the environmental aspect, the coal consumption, CO2 and SO2 emission can reduce by 7.35 %, 7.34 % and 7.35 %, respectively. The result shows that the improved system can decrease the curtailed wind power significantly and boost the CHP operation flexibility remarkably. Meanwhile, the dynamic behaviors of system components in reasonable scope mean that the fluctuant renewable energy can be eliminated efficiently, validating the effectiveness of the proposed system in high shared wind region simultaneously. Highlights: A hybrid system consisting of CH-CAES and electrical boiler is proposed. The wind power penetration and CHP heat-power decoupling purposes can be achieved. Multi-objective optimization of hybrid system is executed to select optimal plan. This hybrid system has superior performance on multi-dimension based 4E analysis.